Pengurusan strategik harta tanah Perbadanan Setiausaha Kerajaan Johor - Sahid, Mohd. Shahrizan (2016)
State Secretary of Johor Incorporation (hereinafter referred as „SSI‟) was established under the provisions of the legislation known as the State Secretary Johore (Incorporation) Enactment 1953 (Enactment No.2 of 1953) (hereinafter referred as „the Enactment‟). The main objective of the Enactment is to authorise SSI to play its part to hold property including, but not limited to immovable property on behalf of the State Government of Johor. Findings from the National Audit Department in 2010 found that the existence of mismanagement of real estate owned by SSI. The State Public Accounts Committee also conveys their criticism to the SSI‟s administration in order to ensure the management of the assets being implemented efficiently. To date, there are nearly 4,268 titles and 430 new plots of land that have been received by SSI via the process of alienation of land from the State Government of Johor. This figure is expected to increase and growing from year to year. Therefore, this study was carried out to achieve two objectives, namely (1) to study the problems inherent in managing the property of SSI and (2) to identify recommendations and suggestions for improvement that should be taken to strengthen the management of the assets. The data collections in this study are obtained through the interview process involving ten respondents. These data were analysed qualitatively using Analytical Methods Analysis. Results from the study found eight problems in the management of the SSI‟s assets. Finally, the improvement measures from this study are expected to improve the efficiency and professionalism of the SSI in the property management.